Waterland - Swift, Graham, 1949- (New York : Vintage Books, 1992)
Set in the bleak Fen Country of East Anglia, and spanning some 240 years in the lives of its haunted narrator and his ancestors, Waterland is a book that takes in eels and incest, ale-making and madness, the heartless sweep of history and a family romance as tormented as any in Greek tragedy. "" Waterland , like the Hardy novels, carries with all else a profound knowledge of a people, a place, and their interweaving ... Swift tells his tale with wonderful contemporary verve and verbal felicity ... A fine and original work.""-- Los Angeles Times.
Originally Published by William Heinemann Ltd, Great Britain, in 1983.
ENH
Keywords: History teachers -- Fiction; Mentally ill women -- Fiction; Autobiographical memory -- Fiction; Married people -- Fiction; English literature; Fens, The (England) -- Fiction; Psychological fiction